Mencicip Garam sebelum Makan dapat Membunuh berbagai Macam Penyakit: Studi Takhrij dan Syarah Hadis - Zaid Rahmmatullah Afifuddin; Susanti Vera; Ilim Abdul Halim; Deni Miharja (Gunung Djati Conference Series, 2022)
This study aims to discuss the recommendation of tasting salt before eating. This study uses a qualitative method through literature study and is combined with an analytical approach to science as well as hadith validation and hadith text criticism methods to integrate science. The results of the discussion of this study include that salt is able to help the healing process of illness or injury from an Islamic point of view using the perspective of takhrij and syarah hadith. This study concluded that salt is one of the most useful substances, but consuming too much salt will be detrimental to oneself. Thus, it is important to examine people's views about the efficacy of salt in people's lives.